Capital Flight Repatriation : Investigation of Its Potential Gains for Sub-Saharan African Countries - Fofack, Hippolyte; Ndikumana, Leonce (2012)
Despite the substantial recent increase in capital flows to sub-Saharan Africa (SSA), the sub-continent remains largely marginalized in financial globalization and chronically dependent on official development aid. The current debate on resource mobilization for development financing in Africa has overlooked the problem of capital flight, which constitutes an important untapped source of funds. This paper argues that repatriation of flight capital deserves more attention on economic as well as moral grounds. On the moral side, the argument is that a large proportion of the capital flight legitimately belongs to the African people and therefore must be restituted to the legitimate claimants. The economic argument is that repatriation of flight capital will contribute to propelling the sub-continent on a higher sustainable growth path while preserving its financial stability and independence and without mortgaging the welfare of its future generations through external borrowing. The anticipated gains from capital repatriation are large. In particular, this paper estimates that if only a quarter of the stock of capital flight was repatriated to SSA, the sub-continent would go from trailing to leading other developing regions in terms of domestic investment. The paper proposes some strategies for inducing capital flight repatriation, but cautions that the success of this program is contingent on a strong political will on the part of African and Western governments and effective coordination and cooperation at the global level.